2012
DOI: 10.1186/1746-160x-8-36
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different chlorhexidine pretreatments on adhesion of metal brackets in vitro

Abstract: ObjectiveTo investigate the effect of chlorhexidine applications in various forms and concentrations on adhesion and failure modes of metal brackets in vitro.Material and methodsNinety bovine enamel specimens were allocated to six groups (n=15). Metal brackets were bonded on all specimens after chlorhexidine pre-treatments forming the following groups: (1) untreated specimens (control); (2) 40% varnish (EC40, Biodent BV, Netherlands), remnants removed with brushing mimicking patient cleaning; (3) 40% varnish (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…However, past evidence has demonstrated that the addition of antibacterial components such as chlorhexidine, varnish Liliana Argueta-Figueroa: l_argueta_figueroa@hotmail.com; Rogelio J. Scougall-Vilchis: rogelio_scougall@hotmail.com; Raúl A. Morales-Luckie: ramluckie@hotmail.com; Oscar F. Olea-Mejía: oleaoscar@yahoo.com and gel significantly decreased shear bond strength of the bonding material. 4,5 Currently, a major application of nanotechnology is an antibacterial effect produced by metal nanoparticles (NPs) of either gold, 6 silver, 7 zinc 8 or copper. 9 Copper is significantly more affordable than silver or gold and so it is economically attractive.…”
Section: Introductionmentioning
confidence: 99%
“…However, past evidence has demonstrated that the addition of antibacterial components such as chlorhexidine, varnish Liliana Argueta-Figueroa: l_argueta_figueroa@hotmail.com; Rogelio J. Scougall-Vilchis: rogelio_scougall@hotmail.com; Raúl A. Morales-Luckie: ramluckie@hotmail.com; Oscar F. Olea-Mejía: oleaoscar@yahoo.com and gel significantly decreased shear bond strength of the bonding material. 4,5 Currently, a major application of nanotechnology is an antibacterial effect produced by metal nanoparticles (NPs) of either gold, 6 silver, 7 zinc 8 or copper. 9 Copper is significantly more affordable than silver or gold and so it is economically attractive.…”
Section: Introductionmentioning
confidence: 99%
“…Several investigations have been performed to endow adhesives with antibacterial properties. Owing to their effective antibacterial properties, chlorhexidine and fluorine-containing agents have been previously mixed with adhesives; however, the release of the active component limits the duration of their effect and may influence the mechanical characteristics of the adhesive 21 22 . Furthermore, other Ag-loaded antibacterial materials have been shown to be limited due to discoloration and reduced esthetics 23 24 .…”
mentioning
confidence: 99%
“…The recommended use of CHX mouthwash is twice daily (morning and evening) oral rinsing for 30 s after toothbrushing [55]. Previous studies have shown that use of CHX mouthwash can result in better oral hygiene and lower the incidence of white spot lesions during orthodontic treatment [57]. According to the anti-biofilm assay, CMC-ClyR-ACP nanogel treatment was not as effective as the CHX treatment; however, this result was contradicted by the surface hardness data, which showed that CMC-ClyR-ACP treatment and CHX treatment resulted in similar %SHL values, a result that was confirmed with the SEM micrographs.…”
Section: Discussionmentioning
confidence: 99%